Forage seed systems in eastern Africa: Challenges and opportunities - Mwendia, Solomon W.; Ohmstedt, U.; Karanja, S.; Notenbaert, An Maria Omer; Peters, Michael; Jones, Christopher S. (2018)
Despite the profound livestock importance in eastern Africa, livestock productivity remains low attributable to a number of challenges. One of the major drawbacks is lack of quality feeds and forages. This results in poor animal performance and suboptimal use of resources. Intertwined with this lack of quality forages is the dearth of forage planting materials - including seed and vegetative propagation – to offer producers improved forages adapted to different ecologies and agricultural context. To alter the landscape, developed forage technologies coupled with awareness creation is needed along the forage value chain to support commercially functioning forage seed systems. With the projected doubling of demand for animal products (meat and milk) in sub-Saharan Africa, the pressure will be exerted on livestock feed resources. This is likely to result in a knock-on demand for forage cultivation and hence forage seed demand. To be successful, the forage seed systems need to be supported by an enabling policy across the region, which include: functional procedures for certification and quality control, publicprivate partnerships for the production and dissemination of planting materials, and technical advice in the management of forages. Availability of proven forage technologies, coupled with awareness creation and facilitative movement of forage seeds across countries would boost forage seed system development in eastern Africa, for increased livestock productivity.